Influences of country of origin (COO), branding, and ethnocentrism on product evaluation : a case study of the Malaysian consumer attitude towards foreign and domestic cars. - Yeo, Ee Ee. (2008)
This study investigates the degree of influence of country of origin (COO), global branding, and ethnocentrism on Malaysians’ preference of cars. The research was primarily based in Malaysia but a secondary research was also carried out in Singapore, with the purpose of examining the differences in attitudes between the two groups of people.